PENGARUH MUTASI TERHADAP KINERJA KARYAWAN PADA PT. PEGADAIAN (PERSERO) KANTOR CABANG MANADO SELATAN - Tiwa, Aprilia; Dua, Iyam L; Joroh, Adelaida (MANAJEMEN ADMINISTRASI BISNIS DAN PEMASARAN, 2024)
The research objective was to determine the effect of mutations on employee performance at PT. Pegadaian (Persero) South Manado Branch Office partially. The research method used is a quantitative research method. The total population is 40 employees, and the sample uses saturation sampling where all the population is used as a sample. The data used are primary data and secondary data. Data collection techniques with questionnaires. Observations and interviews. Data analysis technique used descriptive statistical analysis, total score, regression analysis, correlation coefficient and hypothesis testing using SPSS Statistics 25. The results showed that simultaneously, the mutation variable has a significant effect on employee performance. In this study, it was also shown that by means of the t-test, mutations had an effect on employee performance, with the results showing Y = 38.258 + 0.014 X and the value of R Square = 0.148. Thus it can be stated that there is a significant and positive effect of mutations on employee performance.